The public health benefit and burden of mass drug administration programs in Vietnamese schoolchildren: Impact of mebendazole - Debaveye, Sam; Gonzalez Torres, Claudia Virginia; De Smedt, Delphine; Heirman, Bert; Kavanagh, Shane; Dewulf, Jo (PLOS Neglected Tropical Diseases, 2018)
Author summary Millions of children from developing countries are infected by soil-transmitted helminthiases (STH), an infection of intestinal worms that cause abdominal pain, bad absorption of nutrients from food and a decrease in the amount of red blood cells. This disease can be treated with anthelmintic medication, such as mebendazole, that decreases the intensity of infection and leads to a public health benefit. Because reinfection often occurs within months, regular treatment (every six months) is advised. Given the number of people that are infected with this disease, numerous tablets are required each year to facilitate treatment. However, the industrial production of these tablets can have a negative effect on global human health, e.g. through emissions of fine particulate matter, which should be considered as a public health burden. Our findings suggest that the public health benefit of treating STH with anthelmintic medication is 18,035 times larger than the public health burden associated with pharmaceutical production. However, the conclusion that the health benefits for the patients outweigh the health damage due to resource use and emission from industry may not hold for every medical treatment, therefore we propose a more holistic evaluation of health care programmes, including a broader approach towards human health.